2017
DOI: 10.1158/1541-7786.mcr-17-0012
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic Bodies Elicit Gas6-Mediated Migration of AXL-Expressing Tumor Cells

Abstract: Metastases are a major cause of cancer mortality. AXL, a receptor tyrosine kinase (RTK) aberrantly expressed in many tumors, is a potent oncogenic driver of metastatic cell motility and has been identified as broadly relevant in cancer drug resistance. Despite its frequent association with changes in cancer phenotypes, the precise mechanism leading to AXL activation is incompletely understood. In addition to its ligand growth arrest specific-6 (Gas6), activation of AXL requires the lipid moiety phosphatidylser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Numerous studies in breast cancer models have shown tumorpromoting functions of Gas6 through interactions of the Axl receptor 4,6,24 . In contrast, a recent study using a mouse model of Her2 + breast cancer (MMTV-Neu) showed that Axl-mediated metastasis was ligand independent 25 .…”
Section: Gas6 Expression Weakly Correlates With Axl In Invasive Breasmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies in breast cancer models have shown tumorpromoting functions of Gas6 through interactions of the Axl receptor 4,6,24 . In contrast, a recent study using a mouse model of Her2 + breast cancer (MMTV-Neu) showed that Axl-mediated metastasis was ligand independent 25 .…”
Section: Gas6 Expression Weakly Correlates With Axl In Invasive Breasmentioning
confidence: 99%
“…Gas6/TAMR signaling is a critical component of the innate immune response, functions in phagocytic clearance of apoptotic cells and is an important thrombosis factor. More recently, Gas6 was shown to modulate different cellular events such as proliferation, survival and invasion in vitro [3][4][5] . In vitro studies have suggested that Gas6/ Axl signaling promotes tumor cell survival and invasion, such as osteosarcoma 6 , hepatocellular carcinoma 7 , renal cell carcinoma 8 , and lung cancer 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In the previously mentioned studies, ApoBDs were shown to transfer different molecules (DNA, miRNA and protein) and effectively regulating various aspects of the phagocytosed/recipient cells [46][47][48][49][50]. Other studies have also reported the efficiency of ApoBD contents in mounting cellular responses such as vascular protection and cell migration [51,52]. This evidence of direct, potent cargo-mediated functional consequences highlights the potential of ApoBDs as a drug delivery system.…”
Section: Apobds As a Drug Delivery Platformmentioning
confidence: 81%
“…In leukocytes, AXL and MERTK can promote immunosuppressive signaling that is enhanced by the efferocytosis of apoptotic material (28,31,41). Furthermore, ligand-dependent AXL activity can be amplified by the spatial clustering of phosphatidylserine-bound GAS6 on apoptotic bodies (47) and inhibited by GAS6 binding to proteolytically shed soluble receptor (31). In the context of this prior understanding, our data suggest a model that MAPKi-induced tumor cell killing, combined with an accumulation of GAS6-producing TAMs, a reduction in soluble AXL receptor shed from cancer cells, and an elevation of AXL on the cell surface of cancer cells, collectively leads to enhanced GAS6-mediated signaling in close spatial proximity to TAM.…”
Section: Discussionmentioning
confidence: 99%